Cross‐Linkable and Dual Functional Hybrid Polymeric Electron Transporting Layer for High‐Performance Inverted Polymer Solar Cells. Issue 34 (20th June 2017) - Dong, Sheng; Hu, Zhicheng; Zhang, Kai; Yin, Qingwu; Jiang, Xiaofang; Huang, Fei; Cao, Yong
Abstract : A cross‐linkable dual functional polymer hybrid electron transport layer (ETL) is developed by simply adding an amino‐functionalized polymer dopant (PN4N) and a light crosslinker into a commercialized n‐type semiconductor (N2200) matrix. It is found that the resulting hybrid ETL not only has a good solvent resistance, facilitating multilayers device fabrication but also exhibits much improved electron transporting/extraction properties due to the doping between PN4N and N2200. As a result, by using PTB7‐Th:PC71 BM blend as an active layer, the inverted device based on the hybrid ETL can yield a prominent power conversion efficiency of around 10.07%. More interestingly, photovoltaic property studies of bilayer devices suggest that the absorption of the hybrid ETL contributes to photocurrent and hence the hybrid ETL simultaneously acts as both cathode interlayer material and an electron acceptor. The resulting inverted polymer solar cells function like a novel device architectures with a combination of a bulk heterojunction device and miniature bilayer devices. This work provides new insights on function of ETLs and may be open up a new direction for the design of new ETL materials and novel device architectures to further improve device performance. Abstract : Cross‐linkable dual‐functional hybrid electron‐transport layers are developed that can work as both cathode interlayer and light‐harvesting layer in polymer solar cells, which enhances electron collection and contributes to photocurrent production in the resulting devices. These results may provide new directions for the design of multifunctional interface materials and novel device architectures.